Oral mucosal manifestations in primary and secondary Sjögren syndrome and dry mouth syndrome - Błochowiak, Katarzyna; Olewicz-Gawlik, Anna; Polańska, Adriana; Nowak-Gabryel, Michalina; Kocięcki, Jarosław; Witmanowski, Henryk; Sokalski, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : One of the most important symptoms of Sjögren syndrome is xerostomia. The oral cavity deprived of saliva and its natural lubricative, protective and antibacterial properties is prone to a number of unfavourable consequences. Aim : To present the most important lesions on the oral mucosa in primary and secondary Sjögren syndrome and in dry mouth syndrome. Material and methods: The study group comprised 55 patients including 52 women and 3 men aged 20–72 years (average: 28.25 years). Results : Basing on the accepted criteria, primary Sjögren syndrome was diagnosed in 22 (40%) patients, secondary Sjögren syndrome in 18 (32.7%) patients, and dry mouth syndrome in 15 (27.27%) patients. The physical examination and the examination of the mouth were performed and history was elicited from every patient. Conclusions : The most common pathologies appearing on the oral mucosa in primary and secondary Sjögren syndrome are angular cheilitis, cheilitis, increased lip dryness as well as non-specific ulcerations, aphthae and aphthoid conditions.